Professional Relationship Development Through Nursing Care Delivery System Training in Nursing Education - Aria Pranatha; Abdal Rohim; Khusnul Aini; Ranto Karyanto (Yayasan Adra Karima Hubbi, 2026)
Background. However, a significant